SMA liquid memory metal ultra-high performance anti-slip surface material and preparation method thereof
By using SMA liquid memory metal ultra-high performance anti-slip surface layer material, combined with specific components and preparation methods, the problem of poor adhesion of existing anti-slip materials in rainy and snowy weather is solved, high strength, good anti-slip performance and durability are achieved, and travel safety is significantly improved.
Patent Information
- Application Number
- CN202510015083.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-04
AI Technical Summary
The existing anti-slip materials have poor adhesion in rainy and snowy weather, have a long construction and maintenance time, and are prone to brittle breakage and fall off, which has high maintenance investment, which affects travel safety.
SMA liquid memory metal ultra-high performance anti-slip surface layer materials are used, and the components include tailings carbam, P·O52.5 grade cement, ultra-fine ore powder, modified silicone binder, SMA liquid memory metal and organic inorganic composite early strength agent. Through specific preparation methods and combinations, the bonding strength and durability are improved.
It significantly improves the wear resistance, impact resistance and anti-slip properties of the anti-slip surface material, enhances the bonding strength with ceramic tiles and other materials, shortens the initial settling time, and can achieve high strength and good anti-slip performance after 28 days, meeting the requirements of the anti-slip technical regulations for building ground engineering.
Smart Images

Figure CN119750997A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-skid materials for municipal road engineering, and in particular to an SMA liquid memory metal ultra-high performance anti-skid surface material and a preparation method thereof. Background Art
[0002] At present, most of the floors of public buildings in my country, such as squares or pedestrian bridges, are paved with stone and ceramic tiles. In rainy and snowy weather, the ground is too smooth and pedestrians may slip and get injured easily. Therefore, in actual construction, it is usually necessary to lay anti-slip materials on the surface of stone and ceramic tiles. Common anti-slip materials include ordinary cement mortar, concrete or polymers. However, in the prior art, the adhesion between the ordinary cement mortar and concrete and the ceramic tiles is poor, the construction and maintenance time is long, and the ordinary cement mortar and concrete are easy to break and fall off; and the bonding strength between the polymer and the ceramic tiles is relatively improved, but in general, after 28 days, the bonding strength between the polymer layer and the ceramic tiles is mostly less than 5MPa. The polymer layer is also easily damaged, and the maintenance investment required is also high, which also affects travel safety. To this end, the present application has developed an SMA liquid memory metal ultra-high performance anti-slip surface material with high bonding strength and durability and a preparation method thereof. Summary of the invention
[0003] In view of the above technical problems, the present invention provides an SMA liquid memory metal ultra-high performance anti-slip surface material and a preparation method thereof.
[0004] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which comprises the following components by weight: 54-62 parts of tailings diamond sand, 10-16 parts of P·O52.5 grade cement, 5-9 parts of ultrafine mineral powder, 6-10 parts of modified organic silicon binder, 5-8 parts of SMA liquid memory metal, 0.3-0.7 parts of organic-inorganic composite early strength agent and 6-10 parts of water.
[0005] Preferably, the following ingredients are included in parts by weight: 57 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of water.
[0006] Preferably, the tailings corundum is tailings sand with a particle size of 10 to 20 meshes obtained by crushing and granulating parent rock tailings; the parent rock is one or more of garnet, basalt, and diabase.
[0007] Preferably, the ultrafine mineral powder is blast furnace slag powder of grade S95 or above, and the specific surface area of the ultrafine mineral powder is 600-800m 2 / kg.
[0008] Preferably, the modified organic silicon binder comprises the following components in parts by weight: 35-42 parts of micro-nano quartz powder, 52-57 parts of organic silicon resin emulsion and 3-7 parts of silane coupling agent.
[0009] Preferably, the modified organic silicon binder comprises the following components in parts by weight: 40 parts of micro-nano quartz powder, 55 parts of organic silicon resin emulsion and 5 parts of silane coupling agent.
[0010] Preferably, the modified silicone binder is prepared by the following steps: mixing micro-nano quartz powder, silicone resin emulsion and silane coupling agent, vigorously stirring for 10 to 12 minutes, drying at 60°C to 80°C, and then ball milling to 2000 to 2200 mesh to obtain a modified silicone binder; wherein the stirring speed of the strong stirring is 3000 to 3500 r / min.
[0011] Preferably, the SMA liquid memory metal comprises the following components, measured in parts by weight: 40-45 parts of ferric chloride powder, 3-5 parts of sodium hydroxide, 0.5-2 parts of sodium carboxymethyl cellulose and 50-55 parts of water.
[0012] Preferably, the SMA liquid memory metal comprises the following components, in parts by weight: 42 parts of ferric chloride powder, 4 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 53 parts of water.
[0013] Preferably, the SMA liquid memory metal is prepared by the following steps: A1. Mix ferric chloride powder, sodium hydroxide and sodium carboxymethyl cellulose, and dry-mix for at least 30 seconds to obtain a mixed material; A2. Add water to the mixture and stir for at least 5 minutes to form a homogeneous solution a; wherein the stirring speed is not less than 1200 r / min; A3. Use ultraviolet light with a wavelength range of 10 to 100 nm to directly project it into the homogeneous solution a for at least 10 minutes to obtain an iron molecule liquid memory metal.
[0014] Preferably, the organic-inorganic composite early strength agent comprises 10 to 15 parts of inorganic early strength agent, 1 to 5 parts of organic early strength agent and 85 to 90 parts of polycarboxylate water reducer, the polycarboxylate water reducer is a colorless liquid, and the water reduction rate of the polycarboxylate water reducer is not less than 25%.
[0015] Preferably, the inorganic early strength agent is one or more of sodium sulfate, potassium sulfate, and aluminum sulfate; the organic early strength agent is one or more of triethanolamine, diethanolamine, and triisopropanolamine.
[0016] Preferably, the organic-inorganic composite early strength agent is prepared by the following method: under magnetic stirring conditions, an inorganic early strength agent and an organic early strength agent are sequentially added to a polycarboxylate water reducer, and then stirring is continued for 5 to 8 minutes to obtain an organic-inorganic composite early strength agent.
[0017] A method for preparing an SMA liquid memory metal ultra-high performance anti-slip surface material comprises the following steps: S1. Mix the organic-inorganic composite early strength agent and water according to the predetermined weight proportions, and stir magnetically for at least 2 minutes to obtain solution b; S2, mix the tailing corundum, P·O52.5 grade cement, ultrafine mineral powder and modified silicone binder, dry mix for 30 seconds to mix evenly, and obtain a mixture; S3, adding the SMA liquid memory metal and the solution b obtained in step S1 to the mixture obtained in S2, and continuing to vibrate and stir for 2 to 4 minutes to obtain the SMA liquid memory metal ultra-high performance anti-slip surface material.
[0018] Compared with the prior art, the beneficial effects of the present invention are: 1. The tailings corundum selected in the present invention has a hard texture, which can effectively improve the wear resistance and impact resistance of the ground paved with the SMA liquid memory metal ultra-high performance anti-skid surface material; the single particle size of the tailings corundum makes the SMA liquid memory metal ultra-high performance anti-skid surface material have a larger porosity, thereby having a higher anti-skid performance; 2. The present invention adopts P·O52.5 grade cement to enable the ground paved with SMA liquid memory metal ultra-high performance anti-skid surface material to form strength faster and have higher strength; and the ultra-fine mineral powder not only reacts with the hydration product of P·O52.5 grade cement, calcium hydroxide, to produce volcanic ash, but also fills smaller gaps in P·O52.5 grade cement, so that the ground paved with SMA liquid memory metal ultra-high performance anti-skid surface material forms a denser structure; 3. The modified silicone adhesive of the present invention is prepared from micro-nano quartz powder, silicone resin emulsion and silane coupling agent, wherein the silicone resin emulsion has excellent high temperature resistance, good film-forming property and air-drying property, and has the characteristics of high strength, fast drying and good resistance, but its hardness and dispersibility are poor, and the micro-nano quartz powder can make up for this deficiency, because the micro-nano quartz powder has high density, high hardness and good dispersibility, and can disperse the silicone resin emulsion more uniformly and increase the density. When preparing the SMA liquid memory metal ultra-high performance anti-slip surface material, it can be mixed with cement and tailing corundum more uniformly; in addition, the silane coupling agent in the modified silicone adhesive can form a molecular bridge between the silicone resin and the inorganic substrate (such as laid tiles and marble slabs) to increase the bonding strength.
[0019] 4. The SMA liquid memory metal in the present invention is a saturated solution containing iron ions, which can greatly enhance the strength of the ultra-high performance anti-slip surface material of the SMA liquid memory metal; since ferric chloride is easily hydrolyzed in a solution with low acidity to form iron hydroxide colloid, a small amount of sodium hydroxide is contained in the SMA liquid memory metal of the present application, and the presence of sodium hydroxide can effectively reduce the formation of Fe(OH)3 sol, so that more iron ions can form complexes with water, and since sodium carboxymethyl cellulose has good dispersibility, the sodium carboxymethyl cellulose and water in the SMA liquid memory metal can make the Fe(OH)3 sol formed in the SMA liquid memory metal and the complex formed by iron ions and water better dispersed in the liquid phase composed of sodium carboxymethyl cellulose and water, so that the SMA liquid memory metal is relatively stable. The physical and chemical properties of any substance are determined by the electronic structure or electron cloud of its atoms and molecules. By analyzing the multi-particle Schrödinger equation of all relevant atomic nuclei and electrons, the electronic structure of the atom or molecule can be calculated. By changing its electronic structure and the number of electrons, the properties of the material such as the morphology and function will change accordingly. Light is easily scattered and diffused in the air, but is relatively stable in water, and it is easy to capture the metal ions therein, exerting force on the electron cloud, and then forming more active metal ions. Based on the above, the present invention uses a specific wavelength of ultraviolet irradiation to allow the electron cloud of the iron atom to diffuse in the water, reduce its volume, and form more iron ions. When using SMA liquid memory metal and other components to prepare SMA liquid memory metal ultra-high performance anti-slip surface material, the Fe in the SMA liquid memory metal 3+ Can react with Al in cement 3+ The particles react to form Fe-Al hydrate colloids, which strengthen the strength of the concrete, making the SMA liquid memory metal ultra-high performance anti-slip surface material have higher strength; 5. The SMA liquid memory metal ultra-high performance anti-skid surface material of the present invention adopts an organic-inorganic composite early-strengthening agent. Among the organic-inorganic composite early-strengthening agents, the inorganic early-strengthening agent stimulates the hydration reaction of C3A and C4AF in P·O52.5 grade cement and ultra-fine mineral powder, and the organic early-strengthening agent promotes the hydration reaction of C3S and C2S in P·O52.5 grade cement and ultra-fine mineral powder, forming more hydration products in the early stage, and the early strength is high. The organic-inorganic composite early-strengthening agent described in this application can effectively shorten the initial setting time of the cementitious material without affecting the strength of the ground prepared by the SMA liquid memory metal ultra-high performance anti-skid surface material, and achieve a relatively high strength as soon as possible. In addition, on the basis of the synergistic enhancement of the SMA liquid memory metal and the modified organosilicon binder, the goal of quickly releasing traffic in 4 hours can be achieved by adjusting the setting time of the anti-skid surface material with the organic-inorganic composite early-strengthening agent.
[0020] 6. The SMA liquid memory metal ultra-high performance anti-skid surface material prepared by the present invention has a compressive strength of more than 120MPa, a flexural strength of more than 20MPa, an adhesive strength of more than 20MPa, and an anti-skid performance BPN of more than 70 after being laid and allowed to stand for 28 days. The results obtained in this application in terms of compressive strength, flexural strength, and adhesive strength after the SMA liquid memory metal ultra-high performance anti-skid surface material is laid and allowed to stand for 28 days also show that the SMA liquid memory metal ultra-high performance anti-skid surface material prepared by this application has better durability; this invention not only meets the "Technical Code for Anti-skid of Building Ground Engineering" (JGJ / T 331-2014) for the anti-slip performance of ground stone (pendulum value method ≥60) related regulations, high surface gloss, pollution resistance, and with concrete, marble, ceramic tile, glass, metal and other materials have strong bonding force, various mechanical indicators are far higher than the "Highway Engineering Cement Concrete Rapid Repair Materials Part 1: Cement-based Repair Materials" (JT∕T1211.1-2018) requirements: when developing traffic, the strength requirement should not be less than 70% of the matrix strength for calculation, 28d (ie 28 days) with the benchmark concrete The bonding strength is 2.0MPa, large-scale construction does not shrink, crack, durable, can be passed in as fast as 1h, greatly facilitating travel.
[0021] The SMA liquid memory metal ultra-high performance anti-slip surface material described in the present invention is not only cost-effective, but also widely used, and can be laid on pedestrian bridges, sidewalks, ceramic pavements, marble pavements, steel bridge decks, asphalt pavements and concrete pavements, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a photo of the SMA liquid memory metal ultra-high performance anti-slip surface material prepared in Example 1. DETAILED DESCRIPTION
[0023] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0024] In this application, the anti-skid performance of SMA liquid memory metal ultra-high performance anti-skid surface material is tested using the "Classification and Test Methods for Anti-skid Performance of Ground Stone" (JC / T 1050-2007) and compared with the "Technical Code for Anti-skid of Building Ground Engineering" (JGJ / T 331-2014). Indicators such as compressive strength, flexural strength, and bonding tensile strength are tested in accordance with the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T 1211.1-2018).
[0025] Embodiment 1: An SMA liquid memory metal ultra-high performance anti-skid surface material, comprising the following ingredients by weight: 57 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water; The tailings corundum is tailings sand with a particle size of 10 to 20 meshes obtained by crushing and granulating the tailings of the parent rock; the parent rock is garnet; The modified organic silicone binder comprises the following components, measured in parts by weight: 40 parts of micro-nano quartz powder, 55 parts of organic silicone resin emulsion and 5 parts of silane coupling agent; the modified organic silicone binder is prepared by the following steps: mixing the micro-nano quartz powder, organic silicone resin emulsion and silane coupling agent, vigorously stirring for 10 minutes, drying at 75°C, and then ball milling to 2000 mesh to obtain the modified organic silicone binder; wherein the stirring speed of the strong stirring is 3000r / min.
[0026] The SMA liquid memory metal comprises the following ingredients, measured by weight: 42 parts of ferric chloride powder, 4 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 53 parts of drinking water; the SMA liquid memory metal is prepared by the following steps: A1, mixing ferric chloride powder, sodium hydroxide and sodium carboxymethyl cellulose, dry-mixing and uniformly obtaining a mixture; A2, adding drinking water to the mixture, stirring at a speed of 1200 r / min for 5 minutes, stirring evenly to form a homogeneous solution a; A3, using ultraviolet light with a wavelength range of 80nm to directly project it into the homogeneous solution a for 12 minutes, thereby obtaining an iron molecule liquid memory metal.
[0027] The organic-inorganic composite early strength agent comprises the following components, measured in parts by weight: 10 parts of sodium sulfate powder, 1 part of triethanolamine and 89 parts of polycarboxylic acid water reducer, wherein the polycarboxylic acid water reducer is a colorless liquid, and the water reduction rate of the polycarboxylic acid water reducer is not less than 25%; the organic-inorganic composite early strength agent is prepared by the following method: at 25° C. and under magnetic stirring conditions, an inorganic early strength agent and an organic early strength agent are sequentially added to the polycarboxylic acid water reducer, and then stirring is continued for 5 minutes to stir evenly to obtain the organic-inorganic composite early strength agent.
[0028] A method for preparing an SMA liquid memory metal ultra-high performance anti-skid surface material, wherein the SMA liquid memory metal ultra-high performance anti-skid surface material is the above-mentioned SMA liquid memory metal ultra-high performance anti-skid surface material, and the method for preparing the SMA liquid memory metal ultra-high performance anti-skid surface material comprises the following steps: S1. Mix the organic-inorganic composite early strength agent and drinking water according to the predetermined weight proportions, and stir magnetically for at least 2 minutes to obtain solution b; S2, mix the tailing corundum, P·O52.5 grade cement, ultrafine mineral powder and modified organic silicon binder, and dry mix for 30 seconds to obtain a mixture; S3. Add the SMA liquid memory metal and the solution b obtained in S1 to the mixture obtained in S2, and continue to vibrate and stir for 2 minutes to obtain the SMA liquid memory metal ultra-high performance anti-slip surface material.
[0029] After testing, the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Example 1 has a compressive strength of 124.7 MPa, a flexural strength of 22.8 MPa, and a bonding strength of 21.7 MPa after 28 days of standing still after laying. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T1211.1-2018); the anti-skid performance BPN reaches 75, which meets the technical requirements of the "Technical Code for Anti-skid of Building Ground Engineering" (JGJ / T331-2014) for the anti-skid performance of ground stone (pendulum value method ≥60).
[0030] Embodiment 2: The components of the SWA liquid memory metal in Example 2 are different from those in Example 1, specifically as follows: 43 parts of ferric chloride powder, 4 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 52 parts of drinking water; the preparation method of the SWA liquid memory metal in Example 2 is different from the preparation method of the SWA liquid memory metal in Example 1, specifically as follows: A1, mixing ferric chloride powder, sodium sulfate and sodium carboxymethyl cellulose, dry-mixing and uniformly obtaining a mixed material; A2, adding drinking water to the mixed material, stirring at a speed of 1200r / min for 8min, stirring evenly to form a homogeneous solution a; A3, using ultraviolet light with a wavelength of 80nm to directly project into the homogeneous solution a, the projection time is 12min, and the iron molecule liquid memory metal is obtained.
[0031] The preparation method of the modified organic silicone binder in Example 2 is different from that of the modified organic silicone binder in Example 1, and is specifically as follows: in parts by weight, it includes the following components: 38 parts of micro-nano quartz powder, 57 parts of organic silicone resin emulsion and 5 parts of silane coupling agent; the modified organic silicone binder is prepared by the following steps: mixing the micro-nano quartz powder, organic silicone resin emulsion and silane coupling agent, vigorously stirring for 10 minutes, drying at 75°C, and then ball milling to 2200 mesh to obtain the modified organic silicone binder; the stirring speed of the strong stirring is 3000r / min; The preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the second embodiment is the same as the preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the first embodiment.
[0032] After testing, the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Example 2 has a compressive strength of 131.2 MPa, a flexural strength of 24.3 MPa, and a bonding strength of 25.1 MPa after being laid and left to stand for 28 days. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T1211.1-2018); the anti-skid performance BPN reaches 71, which meets the technical requirements of the "Technical Code for Anti-skid of Building Ground Engineering" (JGJ / T 331-2014) for the anti-skid performance of ground stone (pendulum value method ≥60).
[0033] Embodiment three: The components of the SWA liquid memory metal in Example 3 are different from those in Example 1, specifically as follows: 40 parts of ferric chloride powder, 4 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 55 parts of drinking water; the preparation method of the SWA liquid memory metal in Example 3 is different from the preparation method of the SWA liquid memory metal in Example 1, specifically as follows: A1, ferric chloride powder, sodium sulfate and sodium carboxymethyl cellulose are mixed, and dry-mixed for 30 seconds to obtain a mixed material; A2, drinking water is added to the mixed material, and stirred at a speed of 1500r / min for 8 minutes to stir evenly to form a homogeneous solution a; A3, ultraviolet light with a wavelength of 100nm is directly projected into the homogeneous solution a for 12 minutes to obtain an iron molecule liquid memory metal.
[0034] The preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the third embodiment is the same as the preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the first embodiment.
[0035] After testing, the SMA liquid memory metal ultra-high performance anti-slip surface material prepared in Example 3 has a compressive strength of 120.6 MPa, a flexural strength of 21.1 MPa, and a bonding strength of 20.3 MPa after 28 days of standing still after laying. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T1211.1-2018); the anti-slip performance BPN reaches 73, which meets the technical requirements of the "Technical Code for Anti-slip of Building Ground Engineering" (JGJ / T331-2014) for the anti-slip performance of ground stone (pendulum value method ≥60).
[0036] Embodiment 4: The components of the SWA liquid memory metal in Example 4 are different from those in Example 1, specifically as follows: 45 parts of ferric chloride powder, 3 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 52 parts of drinking water; the preparation method of the SWA liquid memory metal in Example 4 is different from the preparation method of the SWA liquid memory metal in Example 1, specifically as follows: A1, mixing ferric chloride powder, sodium sulfate and sodium carboxymethyl cellulose, dry-mixing and evenly obtaining a mixed material; A2, adding drinking water to the mixed material, stirring at a speed of 1500r / min, stirring evenly to form a homogeneous solution a; A3, using ultraviolet light with a wavelength range of 50nm, directly projecting it into the homogeneous solution a, and the projection time is 15min, so as to obtain an iron molecule liquid memory metal.
[0037] The components and preparation methods of the organic-inorganic composite early strength agent described in Example 4 and Example 1 are different, specifically as follows: the organic-inorganic composite early strength agent component includes 12 parts of sodium sulfate powder, 3 parts of triethanolamine and 85 parts of polycarboxylic acid water reducer, the polycarboxylic acid water reducer is a colorless liquid, and the water reduction rate of the polycarboxylic acid water reducer is 30%; the organic-inorganic composite early strength agent is prepared by the following method: at 28°C and under magnetic stirring conditions, an inorganic early strength agent and an organic early strength agent are sequentially added to the polycarboxylic acid water reducer, and then stirring is continued for 8 minutes to obtain an organic-inorganic composite early strength agent; The preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the fourth embodiment is the same as the preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the first embodiment.
[0038] After testing, the SMA liquid memory metal ultra-high performance anti-slip surface material prepared in Example 4 has a compressive strength of 142.6 MPa, a flexural strength of 29.1 MPa, and a bonding strength of 35.2 MPa after 28 days of standing still after laying. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T1211.1-2018); the anti-slip performance BPN reaches 72, which meets the technical requirements of the "Technical Code for Anti-slip of Building Ground Engineering" (JGJ / T331-2014) for the anti-slip performance of ground stone (pendulum value method ≥60).
[0039] Embodiment five: The components of the SWA liquid memory metal in Example 5 are different from those in Example 1, specifically as follows: 45 parts of ferric chloride powder, 3 parts of sodium hydroxide, 1 part of sodium carboxymethyl cellulose and 52 parts of drinking water; the preparation method of the SWA liquid memory metal in Example 5 is different from the preparation method of the SWA liquid memory metal in Example 1, specifically as follows: A1, ferric chloride powder, sodium sulfate and sodium carboxymethyl cellulose are mixed, and dry-mixed for 30 seconds to obtain a mixed material; A2, drinking water is added to the mixed material, and stirred at a speed of 1500r / min for 10 minutes to stir evenly to form a homogeneous solution a; A3, ultraviolet light with a wavelength of 50nm is directly projected into the homogeneous solution a for 15 minutes to obtain an iron molecule liquid memory metal.
[0040] The preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the fifth embodiment is the same as the preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface layer material in the first embodiment.
[0041] After testing, the SMA liquid memory metal ultra-high performance anti-slip surface material prepared in Example 5 has a compressive strength of 145.2 MPa, a flexural strength of 32.1 MPa, and a bonding strength of 38.9 MPa after 28 days of standing still after laying. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T1211.1-2018); the anti-slip performance BPN reaches 76, which meets the technical requirements of the "Technical Code for Anti-slip of Building Ground Engineering" (JGJ / T331-2014) for the anti-slip performance of ground stone (pendulum value method ≥60).
[0042] Comparative Example 1: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 53 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 9 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 9.5 parts of drinking water.
[0043] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 1 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of tailings diamond sand, ultra-fine mineral powder and drinking water are different.
[0044] In comparative example 1, the tailings corundum was reduced to 53 parts, the ultrafine mineral powder was increased to 9 parts, and the drinking water was increased to 9.5 parts. The SMA liquid memory metal ultra-high performance anti-skid surface material prepared in comparative example 1 had excess slurry. After testing, the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in comparative example 1 had a compressive strength of 127.3MPa, a flexural strength of 20.3MPa, and a bonding strength of 22.6MPa after 28 days of paving. All mechanical indicators far exceeded the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T 1211.1-2018); however, the anti-skid performance BPN was only 45, which did not meet the technical requirements of the "Technical Code for Anti-skid of Building Ground Engineering" (JGJ / T 331-2014) for the anti-skid performance of ground stone (pendulum value method ≥60). This is because too much slurry fills the surface structure, making the surface smooth and flat, resulting in a decrease in anti-slip performance. It can be seen that the mass fraction of tailings corundum cannot be less than 53 parts.
[0045] Comparative Example 2: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 63 parts of tailings diamond sand, 13 parts of P·O52.5 grade cement, 5 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 4.5 parts of drinking water.
[0046] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 2 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of tailings corundum, P·O52.5 grade cement, ultra-fine mineral powder and drinking water are different.
[0047] In comparative example 2, the tailings corundum was increased to 63 parts, and the cement, ultrafine mineral powder and drinking water were reduced to 13 parts, 5 parts and 4.5 parts, respectively. The SMA liquid memory metal ultra-high performance anti-slip surface material prepared in comparative example 2 was loose and difficult to be compacted manually, which would be laborious. Therefore, the mass fraction of tailings corundum cannot be higher than 62 parts.
[0048] Comparative Example 3: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 60 parts of tailings diamond sand, 9 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 9.5 parts of drinking water.
[0049] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 3 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of tailings corundum, P·O52.5 grade cement and drinking water are different.
[0050] In comparative example 3, the cement was reduced to 9 parts, and the tailings corundum was increased to 60 parts and drinking water was increased to 9.5 parts accordingly. The SMA liquid memory metal ultra-high performance anti-skid surface material prepared in comparative example 3 showed an increase in net slurry and overflow, and the upper corundum coating slurry was less and the surface was loose. This is because in single-particle concrete, the cementitious material cement is reduced, the amount of drinking water is increased, and the drinking water ash ratio is large, showing a relatively "segregated" state. Therefore, the mass fraction of cement should be reasonably controlled.
[0051] Comparative Example 4: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 54 parts of tailings diamond sand, 17 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water.
[0052] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 4 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of tailings corundum and P·O52.5 grade cement are different.
[0053] In Comparative Example 4, the cement was increased to 17 parts, and the tailings corundum was reduced to 54 parts accordingly. The SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Comparative Example 4 was difficult to mix and scattered. This is because the cementitious material cement increased, the amount of drinking water remained unchanged, the drinking water ash ratio became smaller, and under the action of the early strength agent, the material became difficult to mix and inhomogeneous. Therefore, the mass fraction of cement should be reasonably controlled.
[0054] Comparative Example 5: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 60 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 5 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water.
[0055] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 5 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of tailings diamond sand and modified silicone binder are different.
[0056] In Comparative Example 5, the modified silicone binder was reduced to 5 parts, and the tailings corundum was increased to 60 parts accordingly. The SMA liquid memory metal ultra-high performance anti-slip surface material prepared in Comparative Example 5 showed the phenomenon of material scattering and difficulty in manual compaction.
[0057] Comparative Example 6: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 55 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 10 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water.
[0058] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 6 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only the difference in the amount of tailings diamond sand and modified silicone binder.
[0059] In Comparative Example 6, the modified organic silicon binder was increased to 10 parts, and the tailings corundum was correspondingly reduced to 54 parts. The SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Comparative Example 6 showed great cohesion and was difficult to level. It can be seen that the dosage of the modified organic silicon binder should be reasonably controlled.
[0060] Comparative Example 7: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 59 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 5 parts of modified organic silicon binder, 4 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water.
[0061] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 7 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 5 is only that the amounts of tailings diamond sand and SMA liquid memory metal are different.
[0062] In Comparative Example 7, the SMA liquid memory metal is reduced to 4 parts, and the tailings corundum is increased to 59 parts accordingly. The final setting time of the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Comparative Example 7 exceeds 6 hours, which is not conducive to fast passage. Therefore, the SMA liquid memory metal should not be added at too low a dosage.
[0063] Comparative Example 8: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 54 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 10 parts of modified organic silicon binder, 9 parts of SMA liquid memory metal, 0.5 parts of organic-inorganic composite early strength agent, and 7.5 parts of drinking water.
[0064] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 8 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 6 is only that the amounts of tailings diamond sand and SMA liquid memory metal are different.
[0065] In comparative example eight, the amount of SMA liquid memory metal is increased to 9 parts, and the amount of tailings corundum is reduced to 54 parts accordingly. After testing, the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in comparative example eight has a compressive strength of 131.9MPa, a flexural strength of 25.7MPa, and a bonding strength of 22.8MPa after being laid and left to stand for 28 days. All mechanical indicators far exceed the requirements of "Rapid Repair Materials for Cement Concrete in Highway Engineering Part 1: Cement-based Repair Materials" (JT / T 1211.1-2018); the anti-skid performance BPN reaches 63, which meets the technical requirements of the "Technical Code for Anti-skid Construction Ground Engineering" (JGJ / T 331-2014) for the anti-skid performance of ground stone (pendulum value method ≥ 60). Although all indicators are excellent, compared with Example 1, the amount of SMA liquid memory metal increases, and the cost increases by 9% accordingly, which is relatively cost-effective.
[0066] Comparative Example 9: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 57 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.2 parts of organic-inorganic composite early strength agent, and 7.8 parts of drinking water.
[0067] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 9 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of the organic-inorganic composite early strength agent and drinking water are different.
[0068] In comparative example 9, the organic-inorganic composite early strength agent is reduced to 0.2 parts, and the drinking water is increased accordingly. After testing, the final setting time of the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in comparative example 9 is 8h, which is not conducive to fast passage. Therefore, the dosage of the organic-inorganic composite early strength agent should not be too low.
[0069] Comparative Example 10: The invention discloses an SMA liquid memory metal ultra-high performance anti-skid surface material, which is composed of the following components by weight: 57 parts of tailings diamond sand, 14 parts of P·O52.5 grade cement, 7 parts of ultrafine mineral powder, 8 parts of modified organic silicon binder, 6 parts of SMA liquid memory metal, 0.8 parts of organic-inorganic composite early strength agent, and 7.2 parts of drinking water.
[0070] The difference between the SMA liquid memory metal ultra-high performance anti-skid surface material in Comparative Example 10 and the SMA liquid memory metal ultra-high performance anti-skid surface material in Example 1 is only that the amounts of the organic-inorganic composite early strength agent and drinking water are different.
[0071] In Comparative Example 10, the organic-inorganic composite early strength agent is increased to 0.9 parts, and the drinking water is reduced accordingly. After testing, the initial setting time of the SMA liquid memory metal ultra-high performance anti-skid surface material prepared in Comparative Example 10 is 15 minutes, which is not conducive to on-site leveling, compaction and other operations. Therefore, the organic-inorganic composite early strength agent should not be added in too high an amount.
[0072] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A SMA liquid memory metal ultra-high performance anti-slip surface material, characterized by: The invention comprises the following ingredients in parts by weight: 54-62 parts of tailings diamond sand, 10-16 parts of P·O52.5 grade cement, 5-9 parts of ultrafine mineral powder, 6-10 parts of modified organic silicon binder, 5-8 parts of SMA liquid memory metal, 0.3-0.7 parts of organic-inorganic composite early strength agent and 6-10 parts of water.
2. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 1, characterized in that: The tailings corundum is tailings sand with a particle size of 10 to 20 meshes obtained by crushing and granulating the tailings of the parent rock; the parent rock is one or more of garnet, basalt, and diabase.
3. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 1, characterized in that: The modified organic silicon adhesive comprises the following components, measured in parts by weight: 35-42 parts of micro-nano quartz powder, 52-57 parts of organic silicon resin emulsion and 3-7 parts of silane coupling agent.
4. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 3 is characterized by: The modified organic silicon adhesive is prepared by the following steps: mixing micro-nano quartz powder, organic silicon resin emulsion and silane coupling agent, vigorously stirring for 10-12 minutes, drying at 60-80°C, and then ball milling to 2000-2200 meshes to obtain the modified organic silicon adhesive.
5. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 1, characterized in that: The SMA liquid memory metal comprises the following components, measured in parts by weight: 40-45 parts of ferric chloride powder, 3-5 parts of sodium hydroxide, 0.5-2 parts of sodium carboxymethyl cellulose and 50-55 parts of water.
6. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 5, characterized in that: The SMA liquid memory metal is prepared by the following steps: A1. Mix ferric chloride powder, sodium hydroxide and sodium carboxymethyl cellulose, and dry-mix to obtain a mixed material; A2. Add water to the mixture and stir for at least 5 minutes to form a homogeneous solution a; A3. Use ultraviolet light with a wavelength range of 10 to 100 nm to directly project it into the homogeneous solution a for at least 10 minutes to obtain an iron molecule liquid memory metal.
7. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 1, characterized in that: The organic-inorganic composite early strength agent comprises 10 to 15 parts of an inorganic early strength agent, 1 to 5 parts of an organic early strength agent and 85 to 90 parts of a polycarboxylate water reducer, and the water reduction rate of the polycarboxylate water reducer is not less than 25%.
8. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 1, characterized in that: The inorganic early strength agent is one or more of sodium sulfate, potassium sulfate, and aluminum sulfate; the organic early strength agent is one or more of triethanolamine, diethanolamine, and triisopropanolamine.
9. The SMA liquid memory metal ultra-high performance anti-slip surface material according to claim 8, characterized in that: The organic-inorganic composite early strength agent is prepared by the following method: adding an inorganic early strength agent and an organic early strength agent to a polycarboxylate water reducer in sequence at 20° C. to 30° C. under stirring conditions, and then continuing to stir for 5 to 8 minutes to obtain the organic-inorganic composite early strength agent.
10. A method for preparing an SMA liquid memory metal ultra-high performance anti-slip surface material, characterized in that: The SMA liquid memory metal ultra-high performance anti-skid surface material is the SMA liquid memory metal ultra-high performance anti-skid surface material according to claim 1, and the preparation method of the SMA liquid memory metal ultra-high performance anti-skid surface material comprises the following steps: S1. Mix the organic-inorganic composite early strength agent and water according to the predetermined weight proportions, and stir magnetically for at least 2 minutes to obtain solution b; S2, mixing the tailing corundum, P·O52.5 grade cement, ultrafine mineral powder and modified organic silicon binder, and dry-mixing them evenly to obtain a mixture; S3, adding the SMA liquid memory metal and the solution b obtained in S1 to the mixture obtained in step S2, and continuing to vibrate and stir for 2 to 4 minutes to obtain the SMA liquid memory metal ultra-high performance anti-slip surface material.